2020
DOI: 10.31487/j.dobcr.2020.01.08
|View full text |Cite
|
Sign up to set email alerts
|

Hard and Soft Tissue Changes in Patients with Borderline Class III Malocclusion after Maxillary Advancement or Mandibular Setback Surgery: A Cross-Sectional Study

Abstract: Background: The primary aim of this study was to assess the esthetic profile and hard and soft tissue changes in patients with borderline class III malocclusion after maxillary advancement or mandibular setback surgery. The secondary aim was also to evaluate the patients’ face attractiveness after different surgical treatment. Materials and Methods: This observational cross-sectional study evaluated 50 patients with borderline class III malocclusion with a mean age of 29 ± 4 years treated from 2014 to 2019. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…37,38 Shortening of the lower anterior facial height had also been observed after BSSRO setback. 37,39,40 Regarding previously reported changes of the facial soft tissues after BSSRO setback, Vahiheh et al 41 found no significant change in the nasolabial angle. Lisboa et al 29 had less change in the lower lip than in the chin area, and no significant change in the paranasal area.…”
Section: Discussionmentioning
confidence: 87%
“…37,38 Shortening of the lower anterior facial height had also been observed after BSSRO setback. 37,39,40 Regarding previously reported changes of the facial soft tissues after BSSRO setback, Vahiheh et al 41 found no significant change in the nasolabial angle. Lisboa et al 29 had less change in the lower lip than in the chin area, and no significant change in the paranasal area.…”
Section: Discussionmentioning
confidence: 87%
“…At Frankfort Horizontal, this shows the downward and forward posture of the chin with reference to the upper face [18]. The quality of the treatment process, the compatibility of the soft tissues and the patient's expectations all affect the postoperative aesthetic outcome [19][20][21]. Statistical analysis: To eliminate inter-observer error, all radiographs were traced and measured by the same investigator and each measurement was repeated after 2 weeks to decrease intraobserver error.…”
mentioning
confidence: 99%